Morphological dependence of hydrothermally synthesized ZnO nanowires on synthesis temperature and molar concentration - Choi, Koang Ouk; Yoon, Sang Hyun; Kim, Won-Seok; Lee, Kyu-Ha; Yang, Cheol-Min; Han, Jong Hun; Kang, Chi Jung; Choi, Young Jin; Yoon, Tae-Sik (WILEY-V C H VERLAG GMBH, 2013)
The hydrothermal synthesis behavior of ZnO nanowire (NW) on carbon nanotubes (CNTs) with respect to molar concentrations of zinc nitrate hexahydrate and hexamethylenetetramine and temperature was investigated. The ZnO NWs could be synthesized with a single-crystalline wurtzite structure and a diameter in the range of tens of nanometers. Their size does not strongly depend on the temperature, while it increases with increasing molar concentration. The NWs tend to have pyramidal shape at a growth front with increasing temperature and molar concentration probably due to enriched Zn2+ ion concentration. This demonstrates the morphological dependence of ZnO NWs on the relative rates between the decomposition of Zn precursor and subsequent oxidation of Zn to ZnO in hydrothermal synthesis.
Keywords: FIELD-EMISSION; GROWTH; ARRAYS; NANOSTRUCTURES